Assessment of predictors of diabetic foot ulcers in a tertiary care hospital of Maharashtra, India: A cross-sectional comparative study - Sunil Kumar Panigrahi; Sagarika Majumdar (Journal of Education and Health Promotion, 2023)
BACKGROUND: The chances of nonhealing foot ulcer among the diabetic is 10-20 times more than people without diabetes. Foot ulcer among diabetes population affects more than 40-60 million globally. There is a dearth of quality data on the factor among the diabetes patients, which hastens the progression of diabetic foot. The study aims to assess the risk factors associated with foot ulcer among the diabetics. MATERIALS AND METHODS: The study was a cross-sectional comparative study in tertiary care hospital in Maharashtra, India. The study population included 200 diabetic foot ulcer patients and 200 of their age and gender matched comparator were patients with diabetes without foot ulcers. The sampling method was stratified random sampling. RESULTS: The mean age of both the groups of patients was around 54 years. Alcohol consumption, physical activity outside home, low foot care practices, irregularity of diabetic medication, and family history of diabetes among mothers were found to be factors associated with diabetes foot ulcer. CONCLUSION: There is a need to stratify the diabetes patients in regular care as per risk categories depending on the presence of above risk factors. This will not only prioritization of diabetes care in terms of future risk but also reduce the progression of complications like diabetes foot and resulting amputation through an active preventive intervention.